Teachers’ reinforcement and students’ perception to the teachers in English classroom - Lestari, Maria Ana Mei (ELT Forum: Journal of English Language Teaching, 2020)
The study focuses on the positive reinforcement that is used by the teachers in each class and students’ perception towards reinforcement itself. This research involved two English teachers and two different classes of year ten students in SMA Kristen YSKI Semarang. To describe the use of reinforcement by the teachers, their teaching process were recorded and observed. Questionnaire and interview were done at the end of the lesson to describe how the students perceive reinforcement. This study is qualitative research. The data showed that the teachers used various types of reinforcement based on the theory of reinforcement by Moore (2007). They are Verbal, Non-verbal, Vicarious, Delayed, and Qualified Reinforcement. They used almost all types of reinforcement, except the Delayed Reinforcement. In general, Non-verbal Reinforcement was mostly used by the teachers. The interview results showed that the students agreed that reinforcement is important and useful for them during teaching and learning process.